Spinocerebellar Ataxia Concepts, Particularities and Generalities - Bozzetto Ambrosi, Patricia (IntechOpen, 2022)
This book is about spinocerebellar ataxia (SCA), which is among the most challenging pathologies in the neurological landscape. It covers basic concepts, functional classification, and new approaches to medical and non-medical treatment including rehabilitation/palliative care approaches. The volume also describes a wide spectrum of generalities and particularities about various forms of clinical and genetic presentations of ACS that have life-threatening characteristics and long-standing presentation with tremendous variability in presentation and clinical severity. In addition, the book presents important aspects of cerebellar anatomy, nutrition impact, genetic subtypes, and functional classification of medical and non-medical interventions related to stem cells, rehabilitation, and palliative care.